Implementasi Chatbot dengan pendekatan Natural Language Processing dan Naïve Bayes dalam meningkatkan layanan perusahaan - Sebayang, Alvin Christoper; Kharisma, Ivana Lucia; Sujjada, Alun; Kamdan, K (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The development of information technology has influenced how organizations provide services to users. Customer service is an activity aimed at ensuring customer satisfaction through the assistance provided by an individual in addressing issues and meeting their needs. However, in certain conditions, customer service may not be able to handle or serve customers, such as outside working hours and recurring general inquiries from users. In this context, Chatbots have become a promising solution to enhance service quality. This study aims to implement a Chatbot with a Natural Language Processing (NLP) approach and Naive Bayes classification method to improve the performance of the Mangcoding web service or PT Anugrah Kreasi Digital. The system development method in this study includes user needs analysis, Chatbot architecture design, NLP model development, and integration with existing web service platforms. The use of NLP methods is expected to improve accuracy so that the Chatbot can understand the users' natural language and provide relevant responses according to their requests. This study uses a qualitative approach to evaluate the performance of the Chatbot in enhancing web services. The results of this study are expected to improve the efficiency of web services through the implementation of a Chatbot with an NLP approach and Naive Bayes classification method, enabling the Chatbot to provide accurate answers. Additionally, it is expected to provide guidance for organizations in utilizing Chatbot technology to improve interactions with users in the context of web-based services.